The Impact of Child Safety Restraint Status and Age in Motor Vehicle Collisions in Predicting Type and Severity of Bone Fractures and Traumatic Injuries. Issue 8 (December 2017) - Loftis, Christopher M.; Sawyer, Jeffrey R.; Eubanks, James W.; Kelly, Derek M.
Abstract : Background: Although morbidity and mortality in children increases in motor vehicle collisions (MVC) if child restraints are not used, no data exist correlating specific injuries with proper or improper use of safety restraints or age. The purpose of this study was to evaluate correlations between childhood MVC injuries, age, and restraint status. Methods: A medical record search for pediatric patients involved in a MVC was conducted at a pediatric hospital (level 1 trauma). Charts were reviewed for demographics and injury-specific information. Patients were grouped by age, restraint use, and injuries. Results: Nine hundred sixty-seven patients ⩽12 years (average age 6.39 y) were identified. Being properly restrained was most common in all age groups except the 4- to 8-year age group in which being improperly restrained was most common. Unrestrained patients were most commonly found in the 9- to 12-year age group. A statistically significant difference was not observed for orthopaedic injuries among the restraint groups, but internal thoracic injuries, open head wound, and open upper extremity wounds were significantly more common in improperly or unrestrained patients. Improperly restrained infants had a significantly higher rate of intracranial bleeds and abrasions than those properly restrained. Unrestrained and improperly restrained 9- to 12-year olds had significantly more open head, open upper extremity, and vascular injuries. When comparing injury types with age groups, upper extremity fractures, femoral fractures, dislocations, and spinal fractures were found to be significantly higher in older children. Conclusions: Preventing orthopaedic injuries in older children may be accomplished by changes in regulations or automotive safety equipment. Rear-facing child safety seats could possibly be improved to prevent head trauma in the youngest patients. There is a continued need to reinforce the importance of proper use of child safety devices to parents. Knowledge of the patient's age, along with restraint status, might aid in diagnosis of less obvious MCV injuries. Level of Evidence: Level III.